2015
DOI: 10.1016/j.aca.2014.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Chemically glycosylation improves the stability of an amperometric horseradish peroxidase biosensor

Abstract: We constructed a biosensor by electrodeposition of gold nano-particles (AuNPs) on glassy carbon (GC) and subsequent formation of a 4-mercaptobenzoic acid self-assembled monolayer (SAM). The enzyme horseradish peroxidase (HRP) was then covalently immobilized onto the SAM. Two forms of HRP were employed: non-modified and chemically glycosylated with lactose. Circular dichroism (CD) spectra showed that chemical glycosylation did neither change the tertiary structure of HRP nor the heme environment. The highest se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 43 publications
3
12
0
Order By: Relevance
“…2 b). We observed the presence of two different N atom populations; one at 400 eV attributed to the protonated amine of EDC and the second at 403 eV indicating the presence of the nitrogen of the sulfo-NHS in accordance with previously reported data [ 22 ]. An intense N binding energy peak at 398 eV corresponding to the N 1s 1/2 orbital was observed in the high-resolution spectra of the protein (Fig.…”
Section: Resultssupporting
confidence: 92%
“…2 b). We observed the presence of two different N atom populations; one at 400 eV attributed to the protonated amine of EDC and the second at 403 eV indicating the presence of the nitrogen of the sulfo-NHS in accordance with previously reported data [ 22 ]. An intense N binding energy peak at 398 eV corresponding to the N 1s 1/2 orbital was observed in the high-resolution spectra of the protein (Fig.…”
Section: Resultssupporting
confidence: 92%
“…The nitrogen binding energy is found in the high‐resolution N1s spectrum at 401.8 ± 0.1 eV in Figure S2 (Supporting Information), which can be assigned to the succinimidyl ester intermediate formed by the reaction of EDC/sulfo‐NHS with the carboxylic acid groups of the SAM and is in accordance to previous literature . A second observed nitrogen species at 399.6 ± 0.1 eV can be attributed to the presence of protonated amine of EDC …”
Section: Resultssupporting
confidence: 87%
“…The peroxidase stability in extracts derived from potato pulp and brewers' spent grain was higher, compared to other the peroxidase‐containing preparations. Previously, it was reported that the glycosylated HRP used for biosensor construction retained 60% of the initial activity after 100 days of storage at 4°C (Hernández‐Cancel et al, ). HRP immobilized on nano‐Au monolayer retained 60% of the initial activity after 1 month of storage (Lei, Hu, Shen, & Yu, ), and the same enzyme conjugated with starch retained 58 and 24% of the initial activity after 21 and 56 days of storage, respectively (Kagliwal & Singhal, ).…”
Section: Resultsmentioning
confidence: 99%